Synthesis and photocatalytic activities of a CuO/TiO2 composite catalyst using aquatic plants with accumulated copper as a template. Issue 4 (15th January 2019) - Lu, Dongfang; Zelekew, Osman Ahmed; Abay, Angaw Kelemework; Huang, Qitang; Chen, Xiaoyun; Zheng, Yushan
Abstract : A CuO/TiO2 photocatalyst was synthesized by using a hydrolysis method. In the synthesis, the Eichhornia crassipes accumulated with copper was used and combined with titanium chloride precursor. Abstract : A CuO/TiO2 composite photocatalyst was synthesized by using a hydrolysis method. In the synthesis of the CuO/TiO2 composite catalyst, the aquatic plant Eichhornia crassipes containing accumulated copper was used and combined with titanium chloride precursor. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-Vis diffuse spectroscopy (DRS), and N2 adsorption–desorption isotherms were used for CuO/TiO2 characterization. The results showed that the CuO/TiO2 synthesized with Eichhornia crassipes as a template had smaller crystallite size (12.6 nm), higher specific surface area (109 m 2 g −1 ), and higher pore volume (0.135 cm 3 g −1 ). The catalytic activity of the CuO/TiO2 composite catalyst was also investigated by the degradation of phenol under ultraviolet (UV) and visible light irradiation, showing excellent catalytic activity. Complete removal of phenol was achieved at 80 and 120 min under UV and visible light sources, respectively. The catalytic performances may be due to the higher porosity and surface area of the composite catalyst. The Eichhornia crassipes aquatic plant also controls the crystal growth and prevents aggregation, which could enhance the catalytic activity. Moreover, the formation of the p–n CuO/TiO2 heterojunction also facilitates the separation of electrons and holes, and improves the photocatalytic activity of the material.